THE USE OF BUSINESS INTELLIGENCE (BI) IN SMALL AND MEDIUM-SIZED ENTERPRISES (SMEs) IN BOSNIA AND HERZEGOVINA - Kasim Tatić; Zijad Džafić; Mahir Haračić; Merima Haračić (Economic Review)
Small and medium-sized enterprises (SME) represent an extremely important aspect for an economy of a country, especially for the economies of developing countries such as Bosnia and Herzegovina (BiH). Increasingly demanding market, process of globalization, advancement of information and telecommunication technology, and an increase in the negotiating power of certain stakeholders such as customers/clients, have caused the need for a better, faster and more efficient system of making day-to-day decisions, both on operational and strategic level. SMEs are not an exception, as confirmed by the research results, which imply that SMEs in BiH, in most cases, do not have the Business Intelligence (BI) system. The research results also suggest that a significant number of SMEs have one or more information systems, such as Enterprise Resource Planning (ERP), Customer Relationship Management (CRM), Data Management Systems (DMS), Warehouse Management System (WMS), which generate the required data into one or more databases, which are the main source of data for The research also confirms that SME companies in BiH recognize the role and importance of BI, but there is a significant number of barriers and obstacles that hinder the implementation of BI system. These key obstacles and barriers relate to the lack of financial resources, insufficient knowledge and management experience, lack of vision and clearly defined strategic goals, insufficiently defined Key Performance Indicators (KPIs) and their requirements.